IMPLEMENTATION OF REGIONAL INNOVATION POLICIES THROUGH THE ROLE OF REGIONAL DEVELOPMENT PLANNING AGENCY (BAPPEDA) RESEARCH AND DEVELOPMENT OF PALEMBANG CITY - Fajar Sentana; M. Nur Budiyanto; Katriza Imania (RADJA PUBLIKA, 2026)
This research aims to analyze the implementation of regional innovation policy in Agency of Planning and Regional Development, Research and Development (Bappeda Litbang) Palembang City. The problem is paying attention to how Bappeda Litbang Palembang City can implement regional innovation policies in Palembang City. In order to approach this problem, theoretical references from George C. Edward III with four dimensions that affect policy implementation, such as communication, resources, disposition, and bureaucratic structure or bureaucratic system. The data were assembled through literature study, observation, and analyzed qualitatively with a descriptive approach. This study deduced that the four dimensions, such as, the communication dimension, the resource dimension, the disposition dimension, and the bureaucratic structure dimension show positive results. However, there are still obstacles discovered, such as the need to strengthen the socialization and education, strengthen the human resources, commitment of regional apparatus leaders and evaluation of innovation implementation